DETERMINAN YIELD OBLIGASI PEMERINTAH INDONESIA - Mukukhawa, Syaffa Alizza; Nirmala, Tiara (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to analyze the factors influencing the yield movement of Indonesian Government Bonds series FR0070 and the yield's response to macroeconomic shocks. Bonds were chosen because of their relatively fixed income, thus lowering the risk compared to stocks. Therefore, yield changes are an important indicator for investors and market participants. The research method used an error correction model. The results show that the BI-Rate and the exchange rate have a significant positive effect on yield in both the short and long term, while foreign exchange reserves and the volatility index (VIX) have a significant negative effect only in the long term. Inflation has no significant effect in either timeframe. These findings support the Arbitrage Pricing Theory, which states that the return of a security is influenced by several macroeconomic factors. This research is important for investors monitoring yield movements as a tool for bond portfolio management.